Effects of chondroitin sulfate proteoglycan 4 (NG2/CSPG4) on soft-tissue sarcoma growth depend on tumor developmental stage - Hsu, Shu-Hsuan Claire (J Biol Chem, 2018)
Sarcomas, and the mesenchymal precursor cells from which they arise, express chondroitin sulfate proteoglycan 4 (NG2/CSPG4). However, NG2/CSPG4's function and its capacity to serve as a therapeutic target in this tumor type are unknown. Here, we used cells from human tumors and a genetically engineered autochthonous mouse model of soft-tissue sarcomas (STSs) to determine NG2/CSPG4's role in STS initiation and growth. Inhibiting NG2/CSPG4 expression in established murine and human STSs decreased tumor volume by almost two-thirds and cell proliferation rate by 50%. NG2/CSPG4 antibody immunotherapy in human sarcomas established as xenografts in mice similarly decreased tumor volume, and expression of a lentivirus blocking NG2/CSPG4 expression inhibited tumor cell proliferation and increased the latency of engraftment. Gene profiling showed that Ng2/Cspg4 deletion altered the expression of genes regulating cell proliferation and apoptosis. Surprisingly, Ng2/Cspg4 deletion at the time of tumor initiation resulted in larger tumors. Gene expression profiling indicated substantial down-regulation of insulin-like growth factor binding protein (Igfbp) genes when Ng2/Cspg4 is depleted at tumor initiation, but not when Ng2/Cspg4 is depleted after tumor initiation. Such differences may have clinical significance, as therapeutic targeting of a signaling pathway such as NG2/CSPG4 may have different effects on cell behavior with tumor progression. NG2/CSPG4 depletion has divergent effects, depending on the developmental stage of sarcoma. In established tumors, IGF signaling is active, and NG2 inhibition targets cell proliferation and apoptosis.